1975
DOI: 10.1289/ehp.751085
|View full text |Cite
|
Sign up to set email alerts
|

Method development and subsequent survey analysis of biological tissues for platinum, lead, and manganese content.

Abstract: An emission spectrochemical method is described for the determination of trace quantities of platinum, lead, and manganese in biological tissues. Total energy burns in an argon-oxygen atmosphere are employed. Sample preparation, conditions of analysis, and preparation of standards are discussed. The precision of the method is consistently better than +/- 15%, and comparative analyses indicate comparable accuracies. Data obtained for experimental rat tissues and for selected autopsy tissues are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1975
1975
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“… (388) Chain members addressed in the derivation of dose coefficients for isotopes of iridium are isotopes of iridium, platinum, osmium, and rhenium. (389) Platinum and osmium are members of the platinum group, which also contains iridium, ruthenium, rhodium, and palladium. These six metals are chemically similar and generally are found together in ores. (390) The systemic biokinetic of ingested, inhaled, or injected platinum have been studied in laboratory animals, mainly rats, and to some extent in human subjects (Durbin et al., 1957; Durbin, 1960; Lange et al., 1973; Smith and Taylor, 1974; Moore et al., 1975a,b,c; Yoakum et al., 1975; Litterst et al., 1976; Hirunuma et al., 1997). Platinum shows a high rate of urinary excretion in the early days after administration.…”
Section: Iridium (Z = 77)mentioning
confidence: 99%
“… (388) Chain members addressed in the derivation of dose coefficients for isotopes of iridium are isotopes of iridium, platinum, osmium, and rhenium. (389) Platinum and osmium are members of the platinum group, which also contains iridium, ruthenium, rhodium, and palladium. These six metals are chemically similar and generally are found together in ores. (390) The systemic biokinetic of ingested, inhaled, or injected platinum have been studied in laboratory animals, mainly rats, and to some extent in human subjects (Durbin et al., 1957; Durbin, 1960; Lange et al., 1973; Smith and Taylor, 1974; Moore et al., 1975a,b,c; Yoakum et al., 1975; Litterst et al., 1976; Hirunuma et al., 1997). Platinum shows a high rate of urinary excretion in the early days after administration.…”
Section: Iridium (Z = 77)mentioning
confidence: 99%
“…Preliminary results will be presented and include the following highlights. At the present time, there is relatively little contamination of platinum in human tissues (72). Absorbed noble metals can traverse the placental barrier in pregnant experimental animals (90).…”
Section: Commentmentioning
confidence: 89%
“…After inhalation of the metal, rats have relativly elevated concentrations in kidney and bone (Moore et al 1975b). Yoakum et al (1975) found renal deposition after oral exposure to diets supplemented with stable platinum sulfate.…”
Section: A General Characteristics and Biological Behaviormentioning
confidence: 99%